STUDY OF DEFECT ON LLDPE PLUG FOR TELON OIL PRODUCTS USING A HAITIAN MOLDING INJECTION MACHINE 1600MA AT PT X - Mochammad Mahardika; Handika Rahmayanti; Abdul Majid (Jurnal Ilmiah Publipreneur, 2020)
The type of plastic packaging that is popular among the public is bottle packaging, plastic bottle packaging always has a bottle cap. Some people only know that the part of the bottle cap is only on the outer cap, even though the plastic bottle cap consists of two types, namely the outer cap (cap) and the inner cap (plug). The plastic material used to make the plug is Linear Low Density Polyethylene (LLDPE), a telon oil plug is produced using an injection molding machine, by inserting plastic pellets into the hopper and then heating it by the barrel, plastic pellets that have melted will be injected into the mold ( print). In the process of making the telon oil plug, a defect was found. From the observation, it is known that several types of defects that occur during the LLDPE oil plug production process include black dot, flashing, and unmould / short shot. Defects that occur during the telon oil plug production process are caused by damage, contamination, and mismatches in the engine parameter settings. The purpose of this study is to determine the causes and solutions of defects that occur in LLDPE telon oil plugs with the HAITIAN 1600MA injection molding machine at PT X. Some solutions are made to reduce defects that occur in telon oil LLDPE plugs is to clean the material reservoir, repair or replace the mold, clean the hopper before loading the material, and set up the barrel parameter 180-230oC, inject pressure 60 bar, holding pressure 30 bar, speed 17.8 seconds.